Economic impact of a hospital cyberattack in a national health system - Portela, Diana (2023)
Funding Information: This paper was supported by the Doctoral Programme in Health Data Science of the Faculty of Medicine at the University of Porto, Portugal [26]. The authors would like to thank e-MAIS (Movimento Associação dos Sistemas de Informação em Saúde), the Portuguese representative to the European Federation of Medical Informatics, for its contribution to the development of this study. Publisher Copyright: © JMIR Publications Inc.. All Rights Reserved.